Swot Analysis on Business Development of BUMG Tumbar Jaya, Tumpok Barat, Matang Kuli District, North Aceh Regency - Husni Kamal; Dabella Yunia (Jurnal Riset Akuntansi Terpadu, 2021)
BUMG is one of the forces that can encourage the creation of economic improvement for Villagers based on the variety of potentials owned and BUMG administrators must be able to manage and develop businesses by looking at existing opportunities and understanding the demand from the community. This research aims to analyze how business development in BUMG Tumbar Jaya. This type of research uses qualitative by direct interview with the headman of Tumpok Barat village and BUMG administrators. The SWOT method used to analyze the data. The conclusion of this research is that BUMG Tumbar Jaya has become a bridge for farmers who lack capital in their business by cooperating with local agricultural shops and should be able to set up their own agricultural stores so that profits become fully owned by Village and need government support to improve human resources in terms of business management and good financial report making.